Estratégias inovadoras para abordagem da imunologia na área de ciências da natureza no ensino médio - Oliveira, Fabiana de (2022)
Concepts related to the areas of cell biology, histology and immunology are subjects seen by biology teachers as "thorny" subjects. With difficult terms, unusual and often with abstract concepts. The teacher's "heartbreak" is easily perceived by the students. When combined with the lack of laboratories equipped with the equipment and materials that many believe to be the only way to teach, the challenge is even greater. With the covid19 pandemic started in 2020, knowledge of immunology has been increasingly mentioned by digital media and various forms of communication. The news related to the subject and a greater scientific dissemination made curiosity popular and common among ordinary people and students. The aim of this study was to develop a material to support biology teachers, using an investigative approach, associated with active methodologies, directed in particular to educational institutions that do not have laboratories. A demonstrative-investigative study was carried out, encouraging the students' protagonism through various activities such as: production of mental map, didactic models and podcast, having an experimental character, with data collection and descriptive statistical analysis, based on action research. The didactic sequence was developed in a State School, in the municipality of Nova Maringá - MT, with the participation of 24 students of the 1st year of high school. In the self-assessment, only 15 students answered the questionnaire, floating the result. It was possible to conclude that the students yearn for dynamic classes, that the Didactic Sequence positively impacted on the learning of the content addressed, was efficient in encouraging the student's protagonism and made the learning significant. The educational product developed was an orientation containing the DS performed, with which it is intended to motivate other fellow teachers of the area to boost their classes.